JEJAK-JEJAK BUDAY A Dl HULU SUNGAI ARUT, KABUPATEN KOTAWARINGIN BARAT, KALIMANTAN TENGAH - Hartatik, nfn (Naditira Widya, 2008)
Along the Arut River, there are ten villages where the Dayak Arut community lives. In each village, there are several tangible and intangible potential cultural heritages. The tangible cultural heritages consist· of sandong, sempunduk, pantar, patung sejahu, and balai antang, which are significant emblems of the Kaharingan belief. The richest cultural heritage can be found in Desa Pandau. In the village, there are three unique heritages: 1) sempuduk decorated with Arabic inscription; 2) pantar pillar and 3) sandong which are decorated with kerayasapa and sa yam. This article discusses some varieties of cultural heritage along the Arut River.